Analisis Peningkatan Kinerja Perusahaan Menggunakan Aplikasi Sistro Pada PT Kharisma Barokah Muliatama Pada Masa New Normal - Ridwan Muhammad Fauzi; Eki Dudi Darmawan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
ABSTRACT This study was conducted to determine the increase in company performance using the Sistro application of PT Kharisma Barokah Muliatama during the New Normal period. In choosing the Sistro Application, PT Kharisma Barokah Muliatama because this application is very influential for the smooth delivery of the company's fertilizer product expedition services to several warehouse areas. The method used in this research is qualitative method. Data were collected through library research, documentation, observation and interviews. The subject of this research is the Sistro application. The results of this study are that the use of the Sistro application at PT Kharisma Barokah Muliatama has been effective in facilitating and expediting the company with several systems in the Sistro application including truck loading scheduling, loading fleet tracking and loading ticket printing. Keywords: Service, Satisfaction, Distribution.